Utility of lidocaine in reducing pain of intramuscular benzathine penicillin G in children with rheumatic heart disease: A randomized, double-blind crossover study - Ni Putu Veny Kartika Yantie; Eka Gunawijaya (Annals of Pediatric Cardiology)
Background: The current recommended secondary prevention of rheumatic fever (RF)/rheumatic heart disease (RHD) includes every 21–28 days injection of benzathine penicillin G (BPG), which causes pain. We evaluated the effect of the coadministration of lidocaine on reducing the pain of BPG injections in children with RF/RHD. Patients and Methods: Children aged 7–18 years who received BPG were eligible for a randomized crossover study. Participants received a secondary prophylaxis dose of intramuscular (IM) BPG with and without additional lidocaine as a diluent (0.2–0.4 mg/kg) and were randomized to the intervention (as a sequence). Participants and staff completing the evaluation were blinded to the sequence. Pain scales were assessed by participants using a Visual Analog Scale (VAS) and staff using the Wong–Baker Faces Pain Scale (WBFPS) at 5 and 60 min after injection. Results: Forty-two children were included in the study. Both lidocaine and aquadest sterile water groups were well matched in baseline characteristics. The pain scores at 5 min after BPG injection were lower when lidocaine was coadministrated: 2 (min–max 1–9) in lidocaine versus 5 (min–max 1–9) in sterile water (P = 0.001) using VAS score and 2 (min–max 0–10) in lidocaine versus 4 (1–8) in sterile water (P = 0.002) using WBFPS. Scores at 60 min after BPG injection showed no differences between treatments with P = 0.551 and P = 0.167, respectively, using VAS and WBFPS. No adverse event was observed. Conclusion: The coadministration of lidocaine as diluent resulted in reduced pain 5 min after IM injection of BPG.